HUBUNGAN KONSUMSI MINUMAN BERKAFEIN DAN NATRIUM DENGAN TEKANAN DARAH PADA PASIEN POLI UMUM PUSKESMAS JEURAM - Tiatulrami; Suci Eka Putri; Mulyani, Itza; Rinawati (Universitas Cokroaminoto Palopo, 2025)
Hypertension is a blood pressure disorder influenced by high caffeine and sodium intake, especially in coastal areas like Seunagan District, which has a high incidence of hypertension. This study aims to examine the relationship between caffeine and sodium consumption and blood pressure among patients at the General Clinic of Jeuram Community Health Center. Using a descriptive-analytic method with a cross-sectional design, the study was conducted in December 2024. The population consisted of 525 outpatients with Non-Communicable Diseases (NCDs) recorded from January to August 2024. A sample of 90 patients was selected through simple random sampling using the Lemeshow formula. Data were collected using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Univariate analysis described the frequency distribution of variables, while bivariate analysis using Chi-square and Odds Ratio tested the hypothesis. The results showed a significant relationship between caffeine and sodium intake and blood pressure. Caffeine consumption increased the risk of blood pressure changes by 3.83 times (p = 0.037; OR = 3.830), and sodium intake raised the risk by 18.21 times (p = 0.001; OR = 18.214).